COVID-19 and cerebrovascular diseases: neuroanatomy and neuropathophysiology overview - Ida Ayu Sri Indrayani; Ida Bagus Kusuma Putra; I Gusti Ngurah Ketut Budiarsa; Nyoman Angga Krishna Pramana; Kumara Tini (Bali Anatomy Journal, 2021)
Background: COVID-19 has expanded globally and has become a health burden for the entire world's population. SARS-CoV-2 as the causative virus, currently does not only cause respiratory disorders, it also involves other organs, including the cerebrovascular system, causing manifestations in the central and peripheral nervous systems. Review: SARS-CoV-2 is classified under the β-coronavirus genus of the Coronaviridae family, and 1 of 4 major protein of its structures, known as spike (S) glycoprotein acts as an important role in promoting the viral invasion process. Olfactory and trigeminal nerves are suggested to be the entry point of SARS-CoV-2 to central nervous system, and promote the disruption of brain cells and vasculatures. Conclusion: Manifestations of cerebrovascular disease are becoming more intense, where there is a dysregulation of the ACE2 receptor to perform its main tasks due to the SARS-CoV-2 invasion. SARS-CoV-2 viruses cause various impairments to cerebrovascular endothelial cells, promote hypercoagulation and increasing the risk of thrombosis, downregulate the host immune cells and cause hyperinflammation as well as cytokine storm, lead to brain damages and further complications.